Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(-12\right)+\left(-13\right)+36+\left(-11\right)=\left(-12-13-11\right)+36\)
\(=\left(-36\right)+36\)
\(=0\)
271-[(-43)+271-(-17)]
=271-(-43)-271+17
=271+43+(-271)+17
=[271+(-271)]+[43+17]
=0+60
=60
k nhá
\(271-[(-43)+271-(-17)]\)
\(=271+43-271-17\)
\(=43-17=26\)
271-[(-43)+271.(-17)]
=271-[(-43)+(-4607)]
=271-(-43)+(-4607)
=271+43+(-4607)
=314+(-4607)
=(-4293)
Chúc bn học tốt
1) 271 - [ - 43 - ( - 271 - 17 )]
= 271 - [ - 43 + 271 + 17 ]
=271+43-271-17
=43-17
=26
2) 6 - 24 - 24 + 48 + 4
=10+48-48
=10
1)\(217-\left[-43-\left(-271-17\right)\right]\\ =217-\left(-43+271+17\right)\\ =217+43-271-17\\ =43-17=26\)
2)\(6-24-24+48+4=6+4=10\)
271 - [ ( -43 ) + 271 - ( -17 )
= 271 - [ -43 + 271 + 17 ]
= 271 + 43 - 271 - 17
= ( 271 - 271 ) + ( 43 - 17 )
= 0 + 26
= 26
= 271 + 43 - 271 - 17
= ( 271 - 271 ) + ( 43 -17 )
= 0 + 26
= 26
a,-(168+325) + ( 168 + 425 )
= -168 - 325 + 168 + 425
= [ ( -168 ) + 168 ] + [ ( -325 ) + 425]
= 0 + 100
= 100
a, (38 - 29 + 43) - (43 + 38)
= 38 - 29 + 43 - 43 - 38
= (38 - 38) + (43 - 43) - 29
= -29
b, 271 - [(-43) + 271 - (-17)]
= 271 - (-43 + 271 + 17)
= 271 + 43 - 271 - 17
= (271 - 271) + (43 - 17)
= 26
@Dương Taurus
c, (-11)2.3 - [3 - (-50).(-4)]
= 121.3 - [(3 + 50.(-4)]
= 363 - 3 + 200
= 560
d, 4.52 + 81.32 - (13 - 4)2
= 4.25 + 81.9 - 132 + 42
= 100 + 729 - 169 + 16
= 676
@Dương Taurus